The Effect of the Use of Canva Interactive Media on the Critical Thinking Ability of Science Learning Students in Class VI of SD Inpres 1 Tondo - Sri Novriyanti; Azizah Azizah; Nuraini Nuraini; Abdul Rahman; Roberto Rolly Bulalong (FKIP - Universitas Riau, 2026)
Critical thinking is an essential competency that should be developed in elementary education to support students in solving problems and making informed decisions. However, students' critical thinking skills in Natural and Social Sciences (IPAS) remain relatively low due to the limited use of interactive digital learning media. This study aimed to examine the effect of Canva-based interactive learning media on the critical thinking skills of sixth-grade students at SD Inpres 1 Tondo. A quantitative approach with a pre-experimental method employing a One Group Pretest–Posttest Design was used. The participants consisted of 14 sixth-grade students selected through total sampling. Data were collected using a multiple-choice critical thinking test and analyzed using descriptive statistics and the Paired Sample t-test with SPSS version 25. The findings revealed that the mean score increased from 61.79 on the pretest to 71.79 on the posttest, representing an improvement of 10.00 points. The Paired Sample t-test indicated a statistically significant difference between the pretest and posttest scores (p < 0.001). These findings demonstrate that Canva-based interactive learning media effectively enhance students' critical thinking skills and can serve as an innovative digital learning medium to support more engaging and meaningful IPAS instruction in elementary schools.